Overview of transport and MHD stability study: focusing on the impact of magnetic field topology in the Large Helical Device. (30th July 2015) - Ida, K.; Nagaoka, K.; Inagaki, S.; Kasahara, H.; Evans, T.; Yoshinuma, M.; Kamiya, K.; Ohdach, S.; Osakabe, M.; Kobayashi, M.; Sudo, S.; Itoh, K.; et al.
Abstract: The progress in the understanding of the physics and the concurrent parameter extension in the large helical device since the last IAEA-FEC, in 2012 (Kaneko O et al 2013 Nucl. Fusion 53 095024), is reviewed. Plasma with high ion and electron temperatures ( T i (0) ∼ T e (0) ∼ 6 keV) with simultaneous ion and electron internal transport barriers is obtained by controlling recycling and heating deposition. A sign flip of the nondiffusive term of impurity/momentum transport (residual stress and convection flow) is observed, which is associated with the formation of a transport barrier. The impact of the topology of three-dimensional magnetic fields (stochastic magnetic fields and magnetic islands) on heat momentum, particle/impurity transport and magnetohydrodynamic stability is also discussed. In the steady state operation, a 48 min discharge with a line-averaged electron density of 1 × 10 19 m −3 and with high electron and ion temperatures ( T i (0) ∼ T e (0) ∼ 2 keV), resulting in 3.36 GJ of input energy, is achieved.